Clinical management and patient outcomes of acute lower gastrointestinal bleeding. A multicenter, prospective, cohort study. Issue 9 (September 2021) - Radaelli, Franco; Frazzoni, Leonardo; Repici, Alessandro; Rondonotti, Emanuele; Mussetto, Alessandro; Feletti, Valentina; Spada, Cristiano; Manes, Gianpiero; Segato, Sergio; Grassi, Eleonora; Musso, Alessandro; Di Giulio, Emilio; et al.
Abstract: Background & aim: Although acute lower GI bleeding (LGIB) represents a significant healthcare burden, prospective real-life data on management and outcomes are scanty. Present multicentre, prospective cohort study was aimed at evaluating mortality and associated risk factors and at describing patient management. Methods: Adult outpatients acutely admitted for or developing LGIB during hospitalization were consecutively enrolled in 15 high-volume referral centers. Demographics, comorbidities, medications, interventions and outcomes were recorded. Results: Overall 1, 198 patients (1060 new admissions;138 inpatients) were included. Most patients were elderly (mean-age 74±15 years), 31% had a Charlson-Comorbidity-Index ≥3, 58% were on antithrombotic therapy. In-hospital mortality (primary outcome) was 3.4% (95%CI 2.5–4.6). At logistic regression analysis, independent predictors of mortality were increasing age, comorbidity, inpatient status, hemodynamic instability at presentation, and ICU-admission. Colonoscopy had a 78.8% diagnostic yield, with significantly higher hemostasis rate when performed within 24-hours than later (21.3% vs.10.8%, p  = 0.027). Endoscopic hemostasis was associated with neither in-hospital mortality nor rebleeding. A definite or presumptive source of bleeding was disclosed in 90.4% of investigated patients. Conclusion: Mortality in LGIB patients is mainly related to age and comorbidities. Although early colonoscopy has a relevant diagnostic yield and is associated with higher therapeutic intervention rate, endoscopic hemostasis is not associated with improved clinical outcomes [ClinicalTrial.gov number: NCT 04364412].